2021
DOI: 10.22271/oral.2021.v7.i2a.1178
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gutta Percha removal from different niti rotary file system: An in vitro study

Abstract: The main goal of endodontic retreatment is cleaning and shaping of the root canal with removal of old root filling material. Hand instruments and rotary instruments are mainly used for removing this filling material; as hand instruments are time consuming and tedious so we used rotary instrumentation for removal of gutta percha. The main aim of this study is to compare the relative efficacy of three different NI TI rotary instrumentation systems for removal of gutta-percha from root canal during endodontic ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A study conducted by Adorno et al [ 11 ] reported the incidence of apical microcracks in 50% of mandibular premolars after canal preparation to the apical foramen, which is in accordance with the present study. The occurrence of stress due to successive instrumentation, the low capability of the thin and fragile dentin in the apical area to withstand the mechanical stress produced by direct contact with the instrument tip, and features of the files, such as taper angle, flexibility, and cross-section, may also influence the formation of cracks [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Adorno et al [ 11 ] reported the incidence of apical microcracks in 50% of mandibular premolars after canal preparation to the apical foramen, which is in accordance with the present study. The occurrence of stress due to successive instrumentation, the low capability of the thin and fragile dentin in the apical area to withstand the mechanical stress produced by direct contact with the instrument tip, and features of the files, such as taper angle, flexibility, and cross-section, may also influence the formation of cracks [ 21 ].…”
Section: Discussionmentioning
confidence: 99%